INCIDENCE OF MINOR AILMENTS OF PUERPERIUM AND RELATED KNOWLEDGE AMONG POSTNATAL MOTHERS. - Raj K, Soumya; Rajan, Reshma; Kj, Suvi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to identify the incidence and knowledge of minor ailments of puerperium among postnatal mothers and to develop an information leaflet on the management of minor ailments of puerperium. Methods: A quantitative approach with descriptive design and convenience sampling technique was used in this study. With these methods, the researcher selected 100 postnatal mothers attending Obstetrics and Gynecology ward, AIMS, Kochi. A semi-structured questionnaire along with a checklist was used to assess the knowledge and the incidence of minor ailments among postnatal mothers. Result: The result showed that the common incidence of minor ailments was afterpain (67%), perineal discomfort (50%), constipation (43%), and fatigue (67%). Majority of the postnatal mothers had average knowledge (65%) level, and some of them had good knowledge (21%), and some of them had poor knowledge (14%). Conclusion: The study revealed that the main four problems of minor ailments of puerperium were afterpain, perineal discomfort, constipation, and fatigue. Number of studies from different part of the world, including India, shows that a large proportion of postnatal mother experiences minor ailments of puerperium. This provides evidence for giving importance to minor ailments of puerperium. Researchers also provided a baseline information leaflet on the management of minor ailments of puerperium.